The responsive environment : design, aesthetics, and the human in the 1970s - Busbea, Larry (University of Minnesota Press, 2020)
"In The Responsive Environment, Larry D. Busbea takes up this concept of environment as an object and method of design at the height of its aesthetic, technical, and discursive elaboration. Exploring novel models of environmental perception, patterning, and control as developed by Gregory Bateson, Edward T. Hall, Wolf Hilbertz, György Kepes, Marshall McLuhan, Nicholas Negroponte, Paolo Soleri, and others, he shows how living space was reimagined as a domain capable of modification through input from its newly sensitized inhabitants"--